An HPLC-MS/MS method for the quantification of heat stress-related milk metabolites in milk from Holstein-Friesian cross-bred cows in Tanzania - V Habimana; AS Nguluma; ZC Nziku; CC Ekine-Dzivenu; G Morota; R Mrode; SW Chenyambuga (South African Journal of Animal Science)
The main objective of this study was to develop and validate a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method for the determination and quantification of three metabolites in raw milk samples: creatinine, citrate, and β-hydroxybutyrate (3-BHB). The effect of the temperature-humidity index (THI) on the concentrations of these metabolites was also investigated. The study used 29 Holstein-Friesian × Tanzanian Shorthorn Zebu cross-bred cows of two genotypes from the Tanzania Livestock Research Institute in Tanga, Tanzania. The cows were in their second or third parity and their second or third month of lactation. Chromatographic separation of the three metabolites was performed using a Supelco column (150 × 2.1 mm, 3 µm), with a mobile phase consisting of 1% formic acid and 10 mM ammonium formate in high-performance liquid chromatography (HPLC) water, and 1% formic acid in methanol. Creatinine, citrate, and 3-BHB were measured at 2.13, 2.33, and 2.48 minutes of run time, respectively. The calibration curves were linear and ranged from 0.0025 to 0.64 µg/mL for creatinine, 1.25 to 3.20 µg/mL for citrate, and 0.25 to1.28 µg/mL for 3-BHB. The creatinine (8.44–5.40 µg/mL), citrate (36.54–33.93 µg/mL), and 3-BHB (12.07–8.96 µg/mL) concentrations decreased with an increase in THI from 77 to 83. However, these results were complicated by significant interactions between the THI and the genotype, parity, and months in lactation. In conclusion, this study demonstrates the potential of an HPLC-MS/MS method to estimate creatinine, citrate, and 3-BHB concentrations in milk samples, and shows that heat stress affects the concentrations of these milk metabolites.